Βιβλιοκρισία του: ALICIA SIMPSON – STEPHANOS EFTHYMIADIS (επιμ.), Niketas Choniates. A Historian and a Writer, Geneva 2009 - ΠΑΠΑΔΟΠΟΥΛΟΥ, Θεοδώρα (Byzantina Symmeikta, 2011)
Book review: ALICIA SIMPSON – STEPHANOS EFTHYMIADIS, Niketas Choniates. A Historian and a Writer, La Pomme d’Or, Geneva 2009, pp.272+7 plates.